Lessons learned from delivering an internet intervention for insomnia in an Australian public hospital outpatient setting1. (26th November 2018) - Meaklim, Hailey; Abbott, Jo‐Anne M.; Kennedy, Gerard A.; Murray, Greg; Klein, Britt; Rehm, Imogen
Abstract : Objectives: This study examined the feasibility of delivering an online cognitive behavioural therapy for insomnia intervention (Sleep‐e) within an Australian public hospital outpatient insomnia clinic. Method: This study was conducted as an open trial pilot study. Fifty‐two patients waiting for clinic treatment were invited to participate, with ten commencing and six completing the 7‐week internet intervention. Participants completed a battery of questionnaires regarding their demographic information, sleep and insomnia symptoms, and provided feedback about the program. Exclusion criteria were minimal, and the study allowed for participants to have other health, psychiatric, and sleep disorder co‐morbidities. Results: Post‐program satisfaction results suggested that Sleep‐e was easy to use; participants were satisfied with it; and found it beneficial in improving sleep. Paired samples t tests for the intention‐to‐treat sample indicated reductions in participants' insomnia severity ( p = 0.02) and sleep onset latency ( p = 0.04) from pre‐ to post‐program. However, a larger sample is needed to generalise the results to the wider population. Conclusion: The findings support Sleep‐e as a helpful treatment for insomnia in a public hospital outpatient population for at least a subgroup of patients. However, significant lessons were learned regarding the importance of educating health care providers and patients about novel models of internet service delivery. Potential models of adaptive or blended stepped‐care are discussed to facilitate program implementation. Future research should identify how to implement internet interventions more effectively in public health settings to take advantage of their potential to improve clinical efficiency.